Impact of energy consumption on poverty reduction in Africa - Innocent Okwanya; Patricia O. Abah (CBN Journal of Applied Statistics, 2018)
This study investigates the impact of energy consumption on poverty reduction in a panel of 12 African countries over a period of 1981-2014. Using the Fully Modified Ordinary Least Square (FMOLS) method, the study shows that a long-run negative relationship exists between energy consumption and poverty level, which underscores the importance of energy in poverty reduction in the selected African countries. The result also indicates that other variables such as capital stock and political stability have significant effect on poverty implying that these factors play critical role in reducing poverty. Furthermore, the granger causality test shows that a short-run unidirectional causality runs from energy consumption to poverty. The findings clearly suggest that increasing energy consumption leads to a decline in poverty level. The study therefore recommends that the government in the selected countries should improve infrastructure and maintain political stability in order to maximize the effect of energy consumption on poverty reduction.
Keywords: I32; Q43.; 330; Energy Consumption; Panel Causality; Panel Cointegration; Poverty level